Law of banking : texts: cases: comments - Chianu, Emeka (Benin City : Enslee Books, 1995)
The book discusses problems in the banking industry as lodgment of cash with banks, freezing of accounts, bank drafts, stale cheques, payee's remedy against drawers and drawees of cheques, bank's duty to return uncleared cheques, Bankers' Books Evidence Act, Dishonoured Cheques (Offences) Act and numerous others.
Includes index.
rua 27/03/15, ijb 03/04/2019
Loans
Keywords: Banking law; Law - cases